Ususu Ta’lif al-Mu’jam al-‘Arabi : Mu’jam al-Lughah al-‘Arabiyyah al-Mu’ashirah Li Ahmad Mukhtar Umar - Muttaqin, Ichwanul; Handayani, Khalifaturrosyidah (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
This research aims to explore and understand the compilers of Ahmed Mukhtar Omar's Contemporary Arabic Lexicon in terms of its components and method of composition. This research utilises a qualitative research method with the type of desk research. The data sources used are dictionaries, various books, and articles related to the topic under study. Data collection techniques using documentation techniques. Data analysis uses 3 stages, namely data presentation, data reduction, and drawing conclusions. The results of this research are the components of Ahmed Mokhtar Omar's Contemporary Arabic Language Lexicon: The first part, the main part, and the last part. The contemporary lexicon approach means the types of entries in Ahmed Mokhtar's contemporary Arabic language lexicon consisting of 5 types, the special rules for making entries in Ahmed Mokhtar's contemporary Arabic language lexicon consisting of 14 rules, the rules of arrangement in the classification of Ahmed Mokhtar's contemporary Arabic language lexicon consisting of 5 rules.